Microsoft Blazor Building Web Applications in .NET 6 and Beyond - Himschoot, Peter (Apress, 2021)
Build web applications in C# and Microsoft .NET 6 that run in any modern browser and become a full-stack web developer!. Do all these things using the Microsoft Blazor framework and the techniques shown in this book. New in this edition is coverage of the new and improved Razor syntax, communication with the server using SignalR and/or gRPC, the use of virtualization to load large quantities of data efficiently, deployment and ahead-of-time compilation into WASM, new unit testing features, security using OpenID Connect, and more. Reading this book helps you learn to build user interfaces and present data to a user for display and modification, capturing the user's changes via data binding. The book shows how to access a rich library of .NET functionality such as a component model for building a composable user interface, including how to develop reusable components that can be used across many pages and websites. Also covered is data exchange with a server using REST, SignalR, and gRPC, giving you access to microservices and database services. Blazor provides a fresh take on web development by eliminating the need for you to learn different languages and frameworks for client- and server-side development. Blazor allows C# and .NET to be used on all sides-both server-side and client-side-providing a robust feature set that is well suited toward scalable, enterprise-level applications. With Blazor you can use all your experience in .NET 6 along with thousands existing libraries, right in the browser. This book gets you proficient using this important toolkit for web application development. What You Will Learn Build user interfaces and display data for users to edit Capture user edits and changes via data binding Transfer data back and forth between server and client Communicate with microservices and database services using REST, SignalR, or gRPC Develop reusable components and assemble them into bigger components Use routing to build single-page applications (SPAs) Build stable and maintainable software using unit testing Internationalize your application to reach more users Secure your Blazor application with OpenID Connect Who This Book Is For Experienced .NET developers who want to apply their existing skills toward building professional-quality, client-side web applications that run in any browser and web developers who want to step away from JavaScript and its complexities, and instead use a proven technology (C# and .NET6) that is robust...